Nutritional composition and antioxidant properties of the fruit of Berberis heteropoda Schrenk. - Jixiang Sun; Qian Li; Jianguang Li; Jing Liu; Fang Xu (PLoS ONE, 2022)
Objective This study assessed the major nutrients and antioxidant properties of Berberis heteropoda Schrenk fruits collected from the Nanshan Mountain area of Urumqi City, Xinjiang Uygur Autonomous Region, China. Methods and materials We assessed the basic nutrients, including amino acids, minerals, and fatty acids, and determined the total phenol, flavonoid, and anthocyanin contents of the extracts. Results The analytical results revealed the average water (75.22 g/100 g), total fat (0.506 g/100 g), total protein (2.55 g/100 g), ash (1.31 g/100 g), and carbohydrate (17.72 g/100 g) contents in fresh B. heteropoda fruit, with total phenol, flavonoid, and anthocyanin contents of B. heteropoda fruits at 68.55 mg gallic acid equivalents/g, 108.42 mg quercetin equivalents/g, and 19.83 mg cyanidin-3-glucoside equivalent/g, respectively. Additionally, UPLC-Q-TOF-MSE analysis of polyphenols in B. heteropoda fruit revealed 32 compounds. Conclusion B. heteropoda fruits may have potential nutraceutical value and represent a potential source of nutrition and antioxidant phytochemicals in the human diet.